2020
DOI: 10.1097/shk.0000000000001369
|View full text |Cite
|
Sign up to set email alerts
|

Admission Leukocyte Count is Associated with Late Cardiogenic Shock Development and All-Cause 30-Day Mortality in Patients with St-Elevation Myocardial Infarction

Abstract: Background: Thirty-day mortality in ST-elevation myocardial infarction (STEMI) patients is primarily driven by cardiogenic shock (CS). High neutrophil counts and high neutrophil/lymphocyte ratios (NLR) have previously been associated with mortality in STEMI patients; however, there is only sparse knowledge regarding their association with CS. Purpose: We sought to assess the associations between neutrophil count and NLR with the development of CS as wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 37 publications
1
6
0
Order By: Relevance
“…Indeed, the elevation extent of leukocyte after AMI has been shown to correlate with the infarct size (20) and also the prognosis in patients with AMI. Our present study demonstrated elevated leukocyte was an independent risk factor for 30-day all-cause mortality, consistent with previous studies (21), indicating its prognostic importance in patients with CS complicating AMI.…”
Section: Discussionsupporting
confidence: 93%
“…Indeed, the elevation extent of leukocyte after AMI has been shown to correlate with the infarct size (20) and also the prognosis in patients with AMI. Our present study demonstrated elevated leukocyte was an independent risk factor for 30-day all-cause mortality, consistent with previous studies (21), indicating its prognostic importance in patients with CS complicating AMI.…”
Section: Discussionsupporting
confidence: 93%
“…According to Barron et al, high WBC counts were associated with an increased risk of 30-day all-cause mortality in 975 patients with AMI [25]. In line, WBC count was associated with higher rates of 30-day all-cause mortality, including 1892 patients with STEMI [17]. Ohlmann et al showed an association between elevated CRP levels on admission and longterm mortality in patients after primary percutaneous interventions (PCI) in STEMI [26], which is in line with further studies [27,28].…”
Section: Discussionmentioning
confidence: 96%
“…Elevated WBC counts are generally related to increased mortality in cardiovascular diseases, pursuant to several studies [15,16]. With regard to AMI patients, Klein et al demonstrated that 30-day mortality rates were significantly higher in patients within the highest WBC quartiles, including 1892 patients with an ST-elevation myocardial infarction (STEMI) [17].…”
Section: Introductionmentioning
confidence: 99%
“…WBC, neutrophil counts, etc.) and the ratios of such parameters to each other have been reported to have a prognostic value in patients with coronary artery disease and STEMI [ 16 - 19 ] . The present study has shown an association between the IG count, a simple haemogram parameter, and poor prognosis in STEMI patients.…”
Section: Discussionmentioning
confidence: 99%